Outcomes of patients with confirmed SARS-CoV-2 infection undergoing anesthesia: A pilot study - Pedro Manuel Ferreira Vieira da Silva (2021)
Background: Surgical stress can decrease cellular immunity, which is important for the control of SARS-CoV-2 infection. The present study aims to determine the effects of an anesthetic procedure, taking into account several variabilities of the patients' perioperative period. Methods: This was a prospective observational study of patients (n=25) positive for SARSCoV-2 infection undergoing anesthetic procedure, conducted between March 27 and June 15, 2020. Clinical and anesthesia reports were used for the data collection of pre-operative medical status and intra operative occurrences, respectively. An association between perioperative data and post-operative clinical outcomes was made. Results: A total of 27 patients were enrolled in the study, but 2 of them were excluded because they were children. The median patients' age was 72 years old, 9 were male and ASA ranged from II to IV. Of the 25 patients, 18 (72.0%) of them were asymptomatic when screening for SARS-CoV-2, with 9 (56.3%) developing symptoms in the postoperative period. Patients with pre-operative COVID-19 symptoms had lower probabilities of being discharged alive(p=0.039). Presence of COVID-19 related symptoms before surgery was significantly related to ASA classification(p=0.007), urgency of surgical procedure(p=0.003), risk of surgery(p=0.023), postoperative need for invasive mechanical ventilation(p=0.013) and 60- day postoperative outcome(p=0.024). No relation was found between presence of COVID-19 related symptoms before surgery and age(p=0.501), type of anesthesia(p=0.46), need for intraoperative vasopressor(p=0.999), and care unit destination(p=0.103). Conclusion: Symptomatic patients in the preoperative period have a worse outcome. This study emphasizes the need to screen all the patients for COVID-19 infection before anesthetic procedures.